Effect of mindfulness-based interventions on anxiety, depression, and stress in patients with coronary artery disease: a systematic review and meta-analysis of randomized controlled trials - Abdul Manan, Hanani; Mir, Imtiyaz Ali; Humayra, Syeda; Tee, Rong Yuen; Vasu, Deepak Thazhakkattu (Frontiers in Psychology, 2024)
Background Adopting lifestyle interventions is pivotal in coronary artery disease (CAD) management and prevention to amplify cardiovascular and mental well-being. This study aims to quantify the effect of mindfulness-based interventions (MBIs) on anxiety, depression and stress in CAD patients. Methods A systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted by searching four electronic databases (PubMed, CENTRAL, Scopus, and Science Direct) through December 2023. The risk of bias was assessed using the PEDro tool, and the study outcomes were expressed as standard mean difference at 95% CI. Results Out of 1838 yielded results, eight RCTs involving 623 participants with a mean age of 56.96 ± 4.89 met the prespecified eligibility criteria. The pooled results showed a statistically significant and beneficial effect of MBIs on CAD patients’ mental health status in regards to anxiety (SMD = −0.83; 95% CI [−1.19, −0.46], p < 0.001), depression (SMD = − 0.86; 95% CI [−1.14, −0.58], p < 0.001), and stress (SMD = −0.69; 95% CI [−1.27, −0.12], p = 0.02). The subgroup sensitivity analyses based on the region (Asia vs. Europe) indicated a statistically non-significant subgroup effect of MBIs on anxiety (I2 = 63.9%, p = 0.10) and depression (I2 = 25.8%, p = 0.25), and a significant effect on stress (I2 = 80.0%, p = 0.03). Although the methodological quality of the trials was generally satisfactory, all studies lacked allocation concealment and blinding. Additionally, gender imbalances, and inadequate follow-up may have potentially compromised the validity of the trials. Conclusion Mindfulness-based interventions are beneficial for improving CAD patients’ anxiety, depression and stress symptoms. Nevertheless, it is imperative to conduct more rigorous and robust studies with an equal gender ratio and long-term follow-up.